Integrating Chinese and Western medicines reduced the incidence of hepatocellular carcinoma in patients with diabetes mellitus: A Taiwanese population-based cohort study. (March 2020) - Lu, Han-Lin; Su, Yuan-Chih; Lin, Mei-Chen; Sun, Mao-Feng; Huang, Sheng-Teng
Graphical abstract: Highlights: Use of CHMs after DM diagnosis was associated with a significantly reduced risk of developing HCC by 41%. The 10-year cumulative incidence of HCC was significantly reduced in DM patients. Adjuvant CHM with antidiabetics exerted a significant protection to reduce the development of HCC in patients with DM. The most frequently prescribed CHMs for DM patients are Liuwei Dihuang Wan and Salvia miltiorrhiza, respectively. Abstract: Objectives: Much epidemiological evidence links diabetes mellitus (DM) to the development of multiple cancers and, in particular, the development of hepatocellular carcinoma (HCC). The aim of this study was to investigate whether Chinese herbal medicine (CHM) reduces the incidence of HCC in patients receiving Western antidiabetic drugs. Interventions and main outcome measures: This retrospective cohort study used data from the National Health Insurance Research Database involving 81, 105 diabetic patients, including 5122 CHM users and 25, 966 non-CHM users. Analyses of treatment effects were adjusted for covariates including gender, age, comorbidities, antidiabetic drugs and liver medications. NodeXL software performed a network analysis to identify the 50 most commonly used CHM herbs and formulas. Results: In Cox proportional hazards models adjusted for demographic and clinical characteristics, DM patients exposed to adjuvant CHM therapy were significantly less likely to develop HCC compared with non-CHM users (adjusted hazard ratio [aHR] 0.59; 95 % confidence interval [CI], 0.41-0.87; p = 0.01). Kaplan-Meier analysis revealed a lower 10-year cumulative risk of HCC among CHM users compared with non-CHM users. Amongst the 10 individual CHM herbs and herbal formulas most commonly prescribed for DM, the most frequent were Salvia miltiorrhiza (Dan Shen) and Liu Wei Di Huang Wan, respectively. Conclusion: This nationwide retrospective cohort study from Taiwan provides some valuable insights into the prescribing characteristics of CHM treatment in patients with DM. Compared with use of Western antidiabetic medications alone, use of adjuvant CHM effectively reduces the incidence of HCC in patients with DM.